One Dimension Model Based Filter for Separation of Time-lapse Microgravity Anomaly - Suhayat Minardi; Teguh Ardianto (Jurnal ILMU DASAR, 2015)
The research has a goal to develop a model-based filter to separate the time lapse microgravity anomali caused by the 3 pieces of the source of anomalies with different depths. The activities which included in this research are: geological modeling, calculation of time lapse microgravity responses caused by several sources, designing of digital model based filter, application of the filter to separate synthetic time lapse microgravity anomali data, and performance test of the filter. Designed model is multi aquifer sistem with homogeny isotropic properties at different depth. Equipment of this research is a unit computer with MATLAB Version 7.11.0.584 (R2010b) and Microsoft Excel 2007 software. The designed filter can separate time lapse microgravity anomali based on its sources successfully with error less than 5%.Keywords: Filter, synthetic, time lapse microgravity anomaly